The Effectiveness of Animated Videos on Knowledge and Attitudes about Sexual Violence Prevention - Zahra, Nabila Isma; Harahap, Reni Agustina; Siregar, Putra Apriadi (Indonesian Journal of Global Health Research, 2024)
Sexual violence in children has until now become a very concerning problem, deviation of sexual violence can occur in any circle. The impact of sexual abuse can torture children to suffer, emotions, depression, loss of appetite, children become introverts, insomnia, cannot focus at school, grades decrease, and even do not move up in class. Objective: To determine the effectiveness of health promotion with animated video media on knowledge and attitudes about preventing sexual violence. The total population was 220 and a sample of 40 students of elementary school 040484 and elementary school 040483 Payung, Kab, Karo using purposive sampling techniques. Method: Quasi Experimental Campbell Design with Nonequivalent Control Group Design research design. Data was collected by distributing questionnaires to respondents. Data analysis using Wilcoxonn test and Mann-Whitney test. Results: The results of the study averaged knowledge about the prevention of sexual violence in children in the video group were pretest (6.95), posttest (8.05), while in the power point group were pretest (8.55), posttest (9.05). The average results of attitudes about preventing sexual violence in children in the video group were pretest (29.45), posttest (35.15), while in the power point group were pretest (33.40), posttest (32.35). Conclusions: There was a difference in the increase in knowledge scores and attitudes about preventing sexual violence in children with animated video media and power points with (p < 0.05).